Evaluation of in vitro and in vivo Glycemic Index of common staples made from varieties of White Yam (Dioscorea rotundata) - Eyinla, Toluwalope Emmanuel; Sanusi, Rasaki Ajani; Maziya-Dixon, Busie (Frontiers in Nutrition, 2022)
Consumption of high Glycemic Index (GI) foods is a risk factor for increasing prevalence of diabetes mellitus (DM). The extent of variation in starch digestibility and GI of Yam varieties and products is not yet fully understood. This study was therefore designed to evaluate in vitro and in vivo Glycemic Index properties of commonly consumed products prepared from varieties of White Yam. Four products (boiled, fried, pounded yam, and Amala) were prepared from 5 common varieties of Yam and evaluated for Digestible Starch (DS) and Resistant Starch (RS). Based on results, two products-pounded yam and Amala-were processed from three of the most popular varieties. Analysis of Rapidly Digestible Starch (RDS), Slowly Digestible Starch (SDS), and estimated in vitro GI (eGI) were then carried out in this stage. Glycemic Index (GI) of these products consumed by apparently healthy young adults were also determined. Variety Amula had highest DS in Amala (19.1/100 g) and pounded Yam (20.4/100 g) while variety Alumaco had highest RS in all the products (2.9–3.3/100 g). When compared with RS in its raw tuber, RS of Alumaco generally increased after processing. Variety Alumaco had lowest RDS in Amala (0.6/100 g) and pounded yam (0.3/100 g) while eGI was lowest in Alumaco made into Amala (53) and pounded yam (48). Assessment of GI resulted in high GI for all products across each variety. Irrespective of variety, processing Yam into Amala released RDS fraction faster when compared with pounded yam. Generally, even though the products are considered as having high GI, Amala raised eGI and GI faster than Pounded yam. Variety-Alumaco particularly showed favorable properties applicable to dietary management of diabetes. Exploring more processing methods and genetic diversity is recommended.